Life Style as Consumer Satisfaction in the Maqāṣid of Islamic Economics: Gaya Hidup sebagai Kepuasan Konsumen dalam Maqāṣid Ekonomi Islam - Siti Musfiqoh (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
Human life will not be separated and is always related to economic activities: production, consumption, and distribution. Activities related to needs and wants A need that is manifested by various desires. In the conventional economic conception, needs and wants are inseparable. Because his stomach is hungry, a person who needs to eat will consider several desires when fulfilling that need. For example, when people feel hungry during the day, East Javanese people will be interested in eating clean vegetables with corn omelet, while others want Rawon with fried meat. Alternatively, people outside Java and even abroad will be different too. A person's desire will be closely related to the concept of satisfaction. On the other hand, in the era of modern society, especially in the era of post-modern society, how a person presents himself in front of others and how a person builds an identity in front of his social environment is in many ways influenced by his lifestyle and his construction in responding to the demands of society and the interests of society—the community behind it. Meanwhile, what kind of lifestyle is developed and displayed by a person in his social environment is generally influenced by the expansion of capital power or the cultural industry that deliberately designs and encourages the development of a lifestyle to benefit capital accumulation profits. Is that right?.